Tuberous Sclerosis Complex: A Roadmap for Future Research - Anna Jeong (Pediatric Neurology Briefs Publishers, 2016)
Investigators from the NINDS and the Tuberous Sclerosis Alliance sponsored a workshop in March 2015, which joined basic scientists and clinicians with expertise in various aspects of Tuberous Sclerosis Complex (TSC), in order to assess the current state of TSC research and to set future goals.